Prevalence and Factors Associated with Harassment in Female Doctors and Nurses in Teaching Hospitals of KPK - Hussain, Hamid; Rehman, Inayat Ur; ., Shukrullah; ., Arusa; Bashir, Sandara; Begum, Mussarat; Jehan, Sumbal; ., Asfa (Journal of Gandhara Medical and Dental Science, 2019)
OBJECTIVES: To determine the prevalence of physical and verbal harassment in nurses and doctors and to evaluate the associated factors which lead to harassment in Teachings Hospitals in Peshawar district in 2018. METHODOLOGY: Nurses and doctors of three government and one private hospital of District Peshawar were included in this study. Sample size was 384. Simple random sampling was used and those nurses and doctors having experience less than 6 months were excluded. A self-administered questionnaire was implemented having both closed and open-ended questions and a written informed consent was taken. Data was analyzed using SPSS version 22. RESULTS: Out of 384 respondents 235 (61.3%) were harassed. Common type was verbal. Prevalence was more in nurses (69.5%) than doctors (52.2%), in non-pathan (73%), Muslim (62%), rural (67.2%), non-married (61.3%), younger age and in surgical and allied (65.5%) nurses and doctors. Main source of harassment were colleagues. More harassment occurs in wards and in night shift and among those nurses and doctors whose daily working hours are more than 8 hours (62.5%) and working experience is more than 4 years (64.6%). CONCLUSION: The prevalence of harassment in our study was 61.3% and significant associated factors of harassment in our study are ethnicity, daily working hours, duration of job, nature of duty, place of duty, religion, work specialty and assailant. KEYWORDS: Physical Harassment, Verbal Harassment, Prevalence, Risk Factors, Lady Doctors, Nurses